2004
DOI: 10.1111/j.1365-3156.2004.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

Features distinguishing amoebic from pyogenic liver abscess: a review of 577 adult cases

Abstract: SummaryDistinguishing amoebic from pyogenic liver abscesses is crucial because their treatments and prognoses differ. We retrospectively reviewed the medical records of 577 adults with liver abscess in order to identify clinical, laboratory, and radiographic factors useful in differentiating these microbial aetiologies. Presumptive diagnoses of amoebic (n ¼ 471; 82%) vs. pyogenic (n ¼ 106; 18%) abscess were based upon amoebic serology, microbiological culture results, and response to therapy. Patients with amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
68
4
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 19 publications
4
68
4
6
Order By: Relevance
“…Thus, we found that in 90% of cases the abscess was unique. Varying percentages have been reported ranging from 65% to 77% [17] [20] [21]. The right lobe remains the preferred but not exclusive location of liver abscesses [9] [12] [22], which is consistent with our findings where abscesses were present in the right lobe in 95%.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, we found that in 90% of cases the abscess was unique. Varying percentages have been reported ranging from 65% to 77% [17] [20] [21]. The right lobe remains the preferred but not exclusive location of liver abscesses [9] [12] [22], which is consistent with our findings where abscesses were present in the right lobe in 95%.…”
Section: Discussionsupporting
confidence: 90%
“…Earlier studies had reported the mean TLC to be 15000cells/mm3 with the range 7500cells/mm3 to 25000cells/mm3. [8] Majority of our patients (86%) had single liver abscess cavity and 94% of our patients had their right lobe involved (Figure No 2).This finding is similar to other studies where solitary abscess and right lobe involvement were most commonly noted [9,10,12,16,17,18] In our study 68% patients had abscess size between 5-8 cm with a mean of 6.5±1.8 (Table 03).It was similar to other studies [6,15,17,19,20] In our study pus culture were positive in 80% patients with E.Coli in 40% cases, Kleibsiella in 10%, staphylococcus in 24% and mixed organism in 06% cases (table no 04). In our study Kleibsiella incidence was less probably due to exclusion of diabetic patients.…”
Section: Discussionsupporting
confidence: 88%
“…In 1987 Barnes et al in a study showed that 22% patients with pyogenic liver abscess had jaundice. [14] But the values obtained by Lodhi et al in Pakistan are different from previous studies, they observed that 43% patients with pyogenic liver abscess had jaundice [9]. Thirty six percent patients had nausea and or vomiting ( Figure No.01).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although the prevalence of alcoholism and diabetes was higher, some studies indicated that amebic infection may depress the human immune system. 1,18,19 Depressed T-cell activity has been found during acute amoebiasis. 1,19 Some parasitic diseases also stimulate a host's immune system to switch from a Th1 to Th2 response.…”
Section: Discussionmentioning
confidence: 99%